Structural stigma, sex work and HIV: contradictions and lessons learnt from a community-led structural intervention in southern India. - Biradavolu, Monica Rao; Blankenship, Kim M; Jena, Asima; Dhungana, Nimesh (Journal of epidemiology and community health, 2012)
Recent theorisation has pushed stigma research in new directions, arguing for a need to challenge the unequal power relations that impact groups most at risk for HIV-related stigma rather than locate stigma in the individual. Such a conceptualisation resonates with the growing emphasis on structural interventions for HIV prevention that attempt to alter the social context of risk.
Keywords: Community Networks; Cross-Sectional Studies; Female; HIV Infections; Humans; India; Interviews as Topic; Organizations; Power (Psychology); Program Evaluation; Prostitution; Qualitative Research; Self Efficacy; Sex Workers; Sexually Transmitted Diseases; Social Stigma; Social Support; Socioeconomic Factors